Hydrocarbon adsorption and desorption composite and method for preparing the same

By forming the enhanced parts of silicate particles on the surface of zeolite particles and combining metal ions, the problem of deterioration of existing hydrocarbon adsorbents in low temperature and high moisture environments is solved, and efficient hydrocarbon adsorption and oxidation capabilities are achieved, which meets strict Emission regulations require.

CN114534689BActive Publication Date: 2025-02-18KOREA UNIV MATHEMATICAL COOP GRP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111406047.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-24
Filing Date
2021-11-24
Publication Date
2025-02-18
Estimated Expiration
2041-11-24

AI Technical Summary

Technical Problem

Existing hydrocarbon adsorbents are difficult to effectively adsorb and oxidize hydrocarbons at low temperatures, and their performance deteriorates in high-water environments, making them unable to meet the strict regulatory requirements for hydrocarbon emissions.

Method used

The gas adsorption part consisting of zeolite particles with low Si/Al ratio is adopted, and a reinforced part consisting of silicate particles is formed on its surface, combining metal ions to improve hydrocarbon adsorption and oxidation capacity, and to increase hydrothermal heat through hydrothermal synthesis stability.

Benefits of technology

It achieves efficient adsorption and oxidation of hydrocarbons at low temperatures and maintains good performance in a high-water environment, meeting the strict regulatory requirements for hydrocarbon emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114534689B_ABST
    Figure CN114534689B_ABST
Patent Text Reader

Abstract

Disclosed is a hydrocarbon adsorption and desorption composite that reduces the emission of hydrocarbon exhaust gas from a vehicle and improves the hydrothermal stability of a device and a method for preparing the same. The hydrocarbon adsorption and desorption composite can have improved hydrocarbon adsorption capacity due to metal ions being bonded to a gas adsorption portion containing aluminum, and can have improved hydrothermal stability due to a reinforcing portion made of silicon dioxide being formed on the surface of the gas adsorption portion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a hydrocarbon adsorption and desorption composite that reduces the emission of hydrocarbon exhaust gas from a vehicle and improves the hydrothermal stability of a device, and more particularly, to a hydrocarbon adsorption and desorption composite in which a reinforcing portion containing silica-zeolite is formed on the surface of a gas adsorption portion including zeolite particles containing aluminum, and a method for preparing the same. Background Art

[0002] With the increasing concern over air pollution, regulations on exhaust gases such as carbon monoxide (CO), nitrogen oxides (NOx), hydrocarbons (HC), and particulate matter (PM) emitted from gasoline and diesel vehicles are being tightened in the United States and Europe, etc. In particular, from Euro 1 in 1992 to Euro 6 in 2020, the emission of hydrocarbons (HC) should be reduced by at least 80% or more compared to that of 1992. In the case of the emission of hydrocarbons (HC) from gasoline vehicles, during the cold start period when the three-way catalyst (TWC, acting on HC oxidation) is not active, hydrocarbons equivalent to 50% to 80% of the hydrocarbons emitted during operation are emitted. Research on hydrocarbon adsorbents (HC traps) is in progress to reduce hydrocarbons emitted during the cold start period. The hydrocarbon adsorbent is a device that adsorbs hydrocarbons emitted during the cold start period and desorbs the adsorbed hydrocarbons when the temperature at which the three-way catalyst is activated (about 200° C. to 300° C.) is reached.

[0003] A large number of studies are underway on the use of zeolites with high physical and chemical stability as hydrocarbon adsorbents. The performance of hydrocarbon adsorbents was tested by measuring the adsorption and desorption of propylene and toluene, which are representative hydrocarbon emissions of gasoline vehicles. Studies on the performance of hydrocarbon adsorbents based on zeolite structure, Si / Al value, and whether or not metal is impregnated were conducted. As the Al content of the zeolite increases (i.e., as the Si / Al value decreases), the amount of hydrocarbons adsorbed to the zeolite increases. In addition, among various zeolite structures, ZSM-5 and β-structured zeolites show high performance. However, due to low hydrocarbon adsorption and oxidation power at temperatures equal to or lower than 300°C, hydrocarbon adsorbents made only of zeolite are unable to fully handle hydrocarbons generated during the cold start period until the temperature at which the three-way catalyst is activated is reached, and have the problem of deterioration of their performance when a large amount of moisture (about 10% by volume) is present.

[0004] In order to solve such problems, the development of an adsorbent that adsorbs and oxidizes hydrocarbons at a temperature lower than the temperature at which the three-way catalyst is activated, exhibits excellent hydrocarbon adsorption and oxidation capabilities even in the presence of a large amount of moisture, and improves the hydrothermal stability of the device is required.

[0005] [Prior art literature]

[0006] [Patent Document]

[0007] (Patent Document 1) Japanese Patent Publication No. 2012-512022 (2012.05.31) Summary of the invention

[0008] One object of the present disclosure is to provide a hydrocarbon adsorption and desorption composite and a method for preparing the same, wherein the hydrocarbon adsorption and desorption composite consists of a gas adsorption part and an enhancement part, wherein the gas adsorption part contains a zeolite having a low silicon to aluminum molar ratio (Si / Al), and the enhancement part contains a zeolite composed of silicon to adsorb a large amount of hydrocarbons during a cold start period and exhibit hydrothermal stability.

[0009] One aspect of the present disclosure provides a hydrocarbon adsorption and desorption composite, comprising: a gas adsorption portion comprising zeolite particles, wherein the zeolite particles have a silicon to aluminum molar ratio (Si / Al) in the range of 1 to 50; and

[0010] a reinforcing portion formed on the surface of the gas adsorption portion, and the reinforcing portion contains silicalite particles having the same structure as the zeolite particles of the gas adsorption portion,

[0011] Herein, metal ions are bound to zeolite particles of the gas adsorption portion, and metal oxides are arranged at the interface between the silicalite particles of the reinforcement portion and the gas adsorption portion.

[0012] Another aspect of the present disclosure provides a method of preparing a hydrocarbon adsorption and desorption composite, comprising: forming a gas adsorption portion by mixing zeolite particles with a solution containing metal ions; and

[0013] adding zeolite particles of the gas adsorption part to a sol solution containing a silicon precursor and a structure directing agent, and performing hydrothermal synthesis on the sol solution for 3 hours to 96 hours to form a reinforcement part,

[0014] The molar ratio of silicon to aluminum (Si / Al) of the zeolite particles in the gas adsorption part is in the range of 1 to 50.

[0015] Since metal ions are bound to the gas adsorption portion containing aluminum, the hydrocarbon adsorption and desorption composite according to the present disclosure can have improved hydrocarbon adsorption capacity, and since the reinforcing portion made of silica is formed on the surface of the gas adsorption portion, the hydrocarbon adsorption and desorption composite can have improved hydrothermal stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 is an image showing a schematic diagram of a hydrocarbon adsorption and desorption composite according to an embodiment of the present disclosure.

[0017] Figure 2 and Figure 3The images are obtained from scanning electron microscopy (SEM) and X-ray diffraction analysis (XRD) patterns of hydrocarbon adsorption and desorption composites according to embodiments of the present disclosure.

[0018] Figure 4 Graph showing results of cold start testing of hydrocarbon adsorption and desorption composites according to embodiments of the present disclosure.

[0019] Figure 5 FIG. 5 is a graph showing the enhancement portion synthesis time, the weight ratio of the enhancement portion to the gas adsorption portion, and the hydrocarbon treatment efficiency based on the hydrocarbon adsorption and desorption composite according to an embodiment of the present disclosure.

[0020] Figure 6 Graphs showing results of cold start tests of hydrocarbon adsorption and desorption composites according to other embodiments of the present disclosure.

[0021] Figure 7 Graphs showing enhancement portion synthesis time, weight ratio of enhancement portion to gas adsorption portion, and hydrocarbon treatment efficiency based on hydrocarbon adsorption and desorption composites according to other embodiments of the present disclosure. DETAILED DESCRIPTION

[0022] Hereinafter, in order to describe the present disclosure in more detail, preferred embodiments according to the present disclosure will be described in more detail with reference to the accompanying drawings. However, the present disclosure can be implemented in other forms and is not limited to the embodiments described herein.

[0023] In the present specification, "total hydrocarbons" means hydrocarbons based on methane. Specifically, it is obtained by converting propylene, toluene, etc. into values ​​corresponding to methane by gas chromatography (GCFID) and quantifying the values ​​as the converted amount of methane.

[0024] The present disclosure provides a hydrocarbon adsorption and desorption composite, comprising: a gas adsorption portion comprising zeolite particles, wherein the molar ratio of silicon to aluminum (Si / Al) of the zeolite particles is in the range of 1 to 50; and

[0025] a reinforcing portion formed on the surface of the gas adsorption portion, and the reinforcing portion contains silicalite particles having the same structure as the zeolite particles of the gas adsorption portion,

[0026] Herein, metal ions are bound to zeolite particles of the gas adsorption portion, and metal oxides are arranged at the interface between the silicalite particles of the reinforcement portion and the gas adsorption portion.

[0027] Figure 1 Schematically shows an image of a hydrocarbon adsorption and desorption composite according to the present disclosure. Figure 1In the present disclosure, the hydrocarbon adsorption and desorption composite includes a gas adsorption part and a reinforcement part, the gas adsorption part is made of zeolite particles with a high aluminum content, and the reinforcement part is made of silica zeolite particles. Specifically, the gas adsorption part can be surrounded by the reinforcement part.

[0028] For example, the hydrocarbon adsorption and desorption composite according to the present disclosure may have a gas adsorption part and a reinforcement part formed in a core-shell structure. In this regard, the core part may be the gas adsorption part, and the shell part may be the reinforcement part.

[0029] Specifically, the molar ratio of silicon to aluminum (Si / Al) of the zeolite particles of the gas adsorption part may be in the range of 1 to 50, in the range of 5 to 50, in the range of 5 to 45, or in the range of 5 to 40. By containing the zeolite particles having the molar ratio of silicon to aluminum as described above, when metal ions are loaded, the metal ions can be bound to the zeolite particles to improve the hydrocarbon adsorption capacity.

[0030] The zeolite particles of the gas adsorption part can independently be at least one zeolite of MFI (Zeolite Socony Mobil-five), β (BEA), chabazite (CHA), KFI, MOR, FAU, FER, AEI, LEV, ERI, AFX, SFW, DDR and LTA, and the reinforcement part can contain the same kind of silica zeolite. The zeolite of the MFI framework structure is a zeolite having a Si / Al value in the range of 10 to 15 or in the range of 10 to 12 and having hydrogen cations bound to the active sites of the zeolite. In addition, β (BEA) zeolite is a zeolite having a Si / Al value in the range of 10 to 25 or in the range of 10 to 20 and having hydrogen cations bound to the active sites of the zeolite.

[0031] When zeolite particles are contained as above, the hydrocarbon adsorption performance of the hydrocarbon adsorption and desorption composite is improved due to the high content of metal ions bound to the inside of the pores of the zeolite, and the hydrocarbon oxidation performance of the hydrocarbon adsorption and desorption composite is improved due to the small size of the metal oxide located at the interface between the zeolite particles.

[0032] The size of the hydrocarbon adsorption and desorption complex may be in the range of 50 nm to 5000 nm. Specifically, the size of the hydrocarbon adsorption and desorption complex may be in the range of 50 nm to 4000 nm, in the range of 100 nm to 2000 nm, or in the range of 200 nm to 1000 nm.

[0033] In addition, micropores exist in the zeolite particles of the gas adsorption part, and metal ions are bound to the inside of the pores existing in the zeolite particles of the gas adsorption part. Specifically, the volume of the micropores of the zeolite particles of the gas adsorption part may be within 0.05 cm 3 / g0.25cm 3 / g, within 0.07cm 3 / g to 0.2cm 3 / g, or within 0.1cm 3 / g to 0.18cm 3 As described above, micropores exist in the zeolite particles, and metal ions are bound to the micropores, so that the adsorption capacity of hydrocarbons such as propylene and toluene can be improved.

[0034] The metal ion may be a cation of at least one metal among the elements of Groups 3 to 12. Specifically, the metal ion may be a cation of one of iron, cobalt, nickel, copper, zinc, rhodium and cadmium. More specifically, the metal ion may be a cation of monovalent iron, divalent iron, trivalent iron, monovalent cobalt, divalent cobalt, monovalent nickel, divalent nickel, monovalent copper or divalent copper.

[0035] In addition, a metal oxide may be arranged at the interface between the silicalite particles of the reinforcing portion and the gas adsorption portion. The metal oxide may be an oxide of at least one metal among the elements of Groups 3 to 12. Specifically, the metal oxide may be an oxide of one of iron, cobalt, nickel, copper, zinc, rhodium and cadmium. More specifically, the metal oxide may be FeO, Fe3O4, Fe2O3, Co3O4, CoO, NiO, Cu2O, Cu2O3 or CuO.

[0036] For example, the metal oxide positioned at the interface between the silicalite particles of the reinforcing portion and the gas adsorption portion may have an average diameter in the range of 1 nm to 10 nm. Specifically, the average diameter of the metal oxide may be in the range of 1 nm to 9 nm, in the range of 1 nm to 7 nm, in the range of 2 nm to 8 nm, or in the range of 2 nm to 6 nm. By positioning the metal oxide as described above at the interface between the silicalite particles of the reinforcing portion and the gas adsorption portion, the hydrocarbon adsorption and desorption composite according to the present disclosure may have a low hydrocarbon oxidation temperature and high hydrothermal stability.

[0037] The hydrocarbon adsorption and desorption composite according to the present disclosure may have a weight ratio of the enhancement portion to the gas adsorption portion in the range of 5 to 95. Specifically, the hydrocarbon adsorption and desorption composite may have a weight ratio of the enhancement portion to the gas adsorption portion in the range of 20 to 90, in the range of 20 to 80, in the range of 15 to 90, in the range of 15 to 80, or in the range of 15 to 60. As described above, by adjusting the weight ratio of the gas adsorption portion and the enhancement portion, it is possible to effectively control the hydrocarbon treatment efficiency and hydrothermal stability of the hydrocarbon adsorption and desorption composite.

[0038] By having the above characteristics, the hydrocarbon adsorption and desorption composite according to the present disclosure may satisfy the following Formula 1:

[0039] [Formula 1]

[0040]

[0041] In the above formula 1,

[0042] Q In represents the total amount of hydrocarbon injected into the hydrocarbon adsorption and desorption complex,

[0043] Q Out represents the total amount of hydrocarbons emitted by the hydrocarbon adsorption and desorption complex, and

[0044] A is a number equal to or greater than 10, and represents hydrocarbon processing efficiency.

[0045] The above formula 1 is a formula for calculating the overall hydrocarbon treatment efficiency of the hydrocarbon adsorption and desorption complex by injecting hydrocarbons into the hydrocarbon adsorption and desorption complex and measuring the amount of the injected and the amount of hydrocarbons discharged from the hydrocarbon adsorption and desorption complex, by means of the ratio of the total amount of hydrocarbons injected into the hydrocarbon adsorption and desorption complex to the total amount of hydrocarbons discharged through the hydrocarbon adsorption and desorption complex up to 300° C. (which indicates that the full three-way catalyst activity has not been reached). In this regard, the overall hydrocarbon treatment efficiency A may be equal to or greater than 10, equal to or greater than 15, equal to or greater than 20, equal to or greater than 25, equal to or greater than 30, equal to or greater than 40, equal to or greater than 50, equal to or greater than 60, or equal to or greater than 70.

[0046] In addition, the hydrocarbon adsorption and desorption composite according to the present disclosure may exhibit hydrocarbon adsorption capability at a temperature equal to or lower than 300°C, and hydrocarbon oxidation capability at a temperature equal to or higher than 200°C. Specifically, the hydrocarbon adsorption and desorption composite according to the present disclosure may exhibit hydrocarbon adsorption capability at a temperature between 70°C and 300°C or at a temperature between 100°C and 300°C, and may exhibit hydrocarbon oxidation capability at a temperature equal to or higher than 210°C, equal to or higher than 220°C, equal to or higher than 230°C, equal to or higher than 240°C, or equal to or higher than 250°C. Typically, 50% to 80% of the total hydrocarbons emitted during driving are emitted during the cold start period (equal to or lower than 300°C). Due to the above characteristics, the hydrocarbon adsorption and desorption composite according to the present disclosure may also effectively adsorb and oxidize hydrocarbons during cold start, and exhibit high hydrothermal stability.

[0047] In addition, the hydrocarbon adsorption and desorption composite according to the present disclosure may have a CH4 / g to 1.5mmol CH4 / g and a hydrocarbon oxidation starting temperature in the range of 180°C to 350°C. Specifically, the hydrocarbon adsorption and desorption composite of the present disclosure may have a hydrocarbon adsorption capacity in the range of 0.1 mmolCH4 / g to 1.3mmol CH4 / g, within 0.3mmol CH4 / g to 1.2mmol CH4 / g, or within 0.3mmol CH4 / g to 0.6mmol CH4 In some embodiments, the invention relates to a hydrocarbon adsorption amount in the range of 100 to 200 ° C., ... oxidation starting temperature in the range of 180 to 320 ° C., a hydrocarbon oxidation starting temperature in the range of 180 to 300 ° C., or a hydrocarbon oxidation starting temperature in the range of 180 to 250 ° C. In this regard, the oxidation starting temperature refers to a temperature at which the amount of CO2 generated relative to the total hydrocarbons is equal to or higher than 5%.

[0048] The hydrocarbon adsorption and desorption composite according to the present disclosure may be subjected to a hydrothermal treatment using 5% to 15% water vapor by volume at a temperature in the range of 600° C. to 900° C. for 1 hour to 96 hours. Specifically, the hydrocarbon adsorbent may be subjected to a hydrothermal treatment at a temperature in the range of 600° C. to 850° C., in the range of 600° C. to 800° C., in the range of 600° C. to 750° C., or in the range of 700° C. to 800° C. for 1 hour to 72 hours, 1 hour to 36 hours, or 5 hours to 30 hours. In this regard, the hourly gas flow rate of the simulated exhaust gas containing water vapor to the weight of the hydrocarbon adsorption and desorption composite may be in the range of 10,000 mL / g·h to 200,000 mL / g·h or in the range of 100,000 mL / g·h to 200,000 mL / g·h. The above situation is a severe situation similar to the situation in the case where the vehicle is running for a long time. A hydrocarbon adsorption and desorption composite that has been subjected to hydrothermal treatment as described above may deteriorate in performance in adsorbing and oxidizing hydrocarbons and may deteriorate in durability in the presence of water vapor.

[0049] For example, the hydrocarbon adsorption and desorption composite that has undergone hydrothermal treatment may have A equal to or greater than 3, equal to or greater than 7, equal to or greater than 10, equal to or greater than 30, or equal to or greater than 40, where A is the overall hydrocarbon treatment efficiency in Formula 1. Although the hydrocarbon adsorption and desorption composite that has undergone hydrothermal treatment shows a lower hydrocarbon treatment efficiency than the hydrocarbon adsorption and desorption composite that has not undergone hydrothermal treatment, the hydrocarbon adsorption and desorption composite including a reinforcing portion made of silicalite shows improved heat resistance after hydrothermal treatment and exhibits excellent adsorption and oxidation capabilities compared to the existing hydrocarbon adsorption and desorption composite having only a gas adsorption portion.

[0050] In addition to the hydrocarbon adsorption performance, the hydrocarbon adsorption and desorption composite according to the present disclosure can also be used in a selective catalytic reduction process (SCR) to effectively remove nitrogen oxides (NO x ) and exhibits air purification capabilities.

[0051] In addition, the present disclosure provides a method for preparing a hydrocarbon adsorption and desorption composite, the method comprising: forming a gas adsorption portion by mixing zeolite particles with a solution containing metal ions; and

[0052] adding zeolite particles of the gas adsorption part to a sol solution containing a silicon precursor and a structure directing agent, and performing hydrothermal synthesis on the sol solution for 3 hours to 96 hours to form a reinforcement part,

[0053] The molar ratio of silicon to aluminum (Si / Al) of the zeolite particles in the gas adsorption part is in the range of 1 to 50.

[0054] The hydrocarbon adsorption and desorption composite prepared using the method for preparing a hydrocarbon adsorption and desorption composite according to the present disclosure may be composed of a gas adsorption portion and an enhancement portion, and the gas adsorption portion and the enhancement portion may be formed in a core-shell structure. In this regard, the core portion may be the gas adsorption portion, and the shell portion may be the enhancement portion.

[0055] In the method for preparing a hydrocarbon adsorption and desorption composite according to the present disclosure, the molar ratio of silicon to aluminum (Si / Al) of the zeolite particles of the gas adsorption part may be in the range of 1 to 50, in the range of 5 to 50, in the range of 5 to 45, or in the range of 5 to 40. By forming the zeolite particles having the molar ratio of silicon to aluminum as described above, when metal ions are loaded, the metal ions can be bound to the zeolite particles to improve the hydrocarbon adsorption capacity.

[0056] Specifically, the zeolite particles of the gas adsorption part may be independently a zeolite of an MFI (Zeolite Socony Mobil-5) framework structure or a β (BEA) zeolite. The MFI framework structure zeolite is a zeolite having a Si / Al value in the range of 10 to 15 or in the range of 10 to 12 and having hydrogen cations bonded to the active sites of the zeolite. In addition, the β (BEA) zeolite is a zeolite having a Si / Al value in the range of 10 to 25 or in the range of 10 to 20 and having hydrogen cations bonded to the active sites of the zeolite.

[0057] When zeolite particles are contained as above, the adsorption capacity of the hydrocarbon adsorption and desorption complex is improved due to the high content of metal ions bound to the inside of the pores of zeolite, and the oxidation performance of the adsorbed hydrocarbons is exhibited due to the small size of the metal oxide formed on the surface of the zeolite particles.

[0058] Forming the gas adsorption portion includes forming the gas adsorption portion by mixing zeolite particles with a metal precursor solution containing metal ions using one of a wet impregnation method, a dry impregnation method, and an ion exchange method as a mixing method, wherein the content of the metal may be in the range of 1 wt % to 9 wt %, in the range of 2 wt % to 8 wt %, in the range of 3 wt % to 8 wt %, or in the range of 4 wt % to 7 wt %. Specifically, forming the gas adsorption portion may include forming zeolite particles impregnated with metal ions using one of a wet impregnation method, a dry impregnation method, and an ion exchange method.

[0059] The solution containing metal ions may contain cations of at least one metal among the elements of Groups 3 to 12. Specifically, the solution containing metal ions may contain cations of one of iron, cobalt, nickel, copper, zinc, rhodium and cadmium. More specifically, the metal ions may be cations of monovalent iron, divalent iron, trivalent iron, monovalent cobalt, divalent cobalt, monovalent nickel, divalent nickel, monovalent copper or divalent copper.

[0060] The metal oxide formed by mixing the solution containing metal ions with the zeolite may be an oxide of at least one metal among the elements of Groups 3 to 12. Specifically, the metal oxide may be an oxide of one of iron, cobalt, nickel, copper, zinc, rhodium and cadmium. More specifically, the metal oxide may be FeO, Fe3O4, Fe2O3, Co3O4, CoO, NiO, Cu2O, Cu2O3 or CuO.

[0061] The zeolite particles can be mixed with a solution containing metal ions to form a mixture, and the mixture can be calcined to form a metal oxide on the zeolite particles. The average diameter of the formed metal oxide can be in the range of 1nm to 10nm. Specifically, the average diameter of the metal oxide can be in the range of 1 to 9nm, in the range of 1 to 7nm, in the range of 2 to 8nm, or in the range of 2 to 6nm. By positioning the metal oxide as described above at the interface between the silica zeolite particles of the reinforcing portion and the gas adsorption portion, the hydrocarbon adsorbent according to the present disclosure can exhibit excellent hydrocarbon adsorption performance, have a low hydrocarbon oxidation temperature, and have high hydrothermal stability.

[0062] The forming of the reinforcing portion may be performed by adding zeolite particles impregnated with metal ions to a sol solution containing a silicon precursor and a structure directing agent, and performing hydrothermal synthesis on the sol solution for 3 hours to 96 hours.

[0063] Specifically, the sol solution may have a molar ratio of silicon precursor:structure directing agent:solvent of 10:1 to 15:10 to 50000, and more specifically, 10:2 to 7:50 to 10000 or 10:1 to 4:100 to 3000.

[0064] Specifically, the silicon precursor as silicon dioxide (SiO2) may be tetramethyl orthosilicate (TMOS), tetraethyl orthosilicate (TEOS), tetrapropyl orthosilicate (TPOS), tetrabutyl orthosilicate (TBOS), fumed silica or colloidal silica, and the solvent may be distilled water (H2O) or ethanol.

[0065] In addition, the organic structure directing agent can be selected from tetrapropylammonium hydroxide (TPAOH), tetraethylammonium hydroxide (TEAOH), N,N,N-trimethyladamantylammonium hydroxide (TMAdaOH), N,N,N-trimethyladamantylammonium bromide (TMAdaBr), N,N,N-trimethyladamantylammonium fluoride (TMAdaF), N,N,N-trimethyladamantylammonium chloride (TMAdaCl), N,N,N-trimethyladamantylammonium iodide (TMAdaI), tetraethylammonium hydroxide (TEAOH), N,N,N-trimethyladamantylammonium bromide (TMAdaBr), N,N,N-trimethyladamantylammonium fluoride (TMAdaF), N,N,N-trimethyladamantylammonium chloride (TMAdaCl), N,N,N-trimethyladamantylammonium iodide (TMA At least one of the group consisting of ethylammonium bromide (TEABr), tetraethylammonium fluoride (TEAF), tetraethylammonium chloride (TEACl), tetraethylammonium iodide (TEAI), tetrapropylammonium bromide (TPABr), tetrabutylphosphonium hydroxide (TBPOH), tetrabutylammonium chloride (TBACl), tetrabutylammonium hydroxide (TBAOH), tetrabutylammonium fluoride (TBAF) and cyclohexylamine, more specifically, tetrapropylammonium hydroxide (TPAOH) or tetraethylammonium hydroxide (TEAOH).

[0066] In addition, in forming the enhanced part, the mixing ratio of the zeolite particles of the gas adsorption part to the sol solution may be in the range of 0.03g / 30mL to 3g / 30mL, in the range of 0.05g / 30mL to 3g / 30mL, in the range of 0.05g / 30mL to 2g / 30mL, in the range of 0.05g / 30mL to 0.5g / 30mL, in the range of 0.05g / 30mL to 0.4g / 30mL, in the range of 0.1g / 30mL to 2g / 30mL, in the range of 0.1g / 30mL to 0.5g / 30mL, in the range of 0.1g / 30mL to 0.5g / 30mL, in the range of 0.15g / 30mL to 1g / 30mL, or in the range of 0.15g / 30mL to 0.35g / 30mL.

[0067] When the reinforcing portion is formed by mixing the sol solution with the zeolite particles of the gas adsorption portion in the same ratio as above, the hydrothermal stability can be improved without impairing the hydrocarbon adsorption capacity by forming the reinforcing portion in an appropriate weight ratio.

[0068] In addition, forming the reinforcing portion may be performed by mixing the zeolite particles of the gas adsorption portion with the sol solution, and performing hydrothermal synthesis on the sol solution at a temperature in the range of 50° C. to 300° C. or in the range of 100° C. to 200° C. for 4 hours to 96 hours, 4 hours to 12 hours, or 24 hours to 48 hours. In this regard, silica zeolite particles having the same structure as the zeolite particles of the gas adsorption portion are formed on the surfaces of the zeolite particles of the gas adsorption portion by the hydrothermal synthesis method.

[0069] As described above, during the metal loading process, metal cation impregnation and metal oxide formation occur in the gas adsorption part, and the enhancement part is formed by silicalite particles, so that the hydrocarbon adsorbent according to the present disclosure can have excellent hydrocarbon adsorption performance, low hydrocarbon oxidation temperature and high hydrothermal stability. In preparing the hydrocarbon adsorbent by the method as above, the hydrocarbon adsorption and desorption composite has a weight ratio of the enhancement part to the gas adsorption part in the range of 5 to 95. Specifically, the hydrocarbon adsorption and desorption composite may have a weight ratio of the enhancement part to the gas adsorption part in the range of 20 to 90, in the range of 20 to 80, in the range of 15 to 90, in the range of 15 to 80, or in the range of 15 to 60. As described above, by adjusting the weight ratio of the gas adsorption part and the enhancement part, it is possible to effectively control the hydrocarbon treatment efficiency and hydrothermal stability of the hydrocarbon adsorption and desorption composite.

[0070] The method for preparing a hydrocarbon adsorbent according to the present disclosure may further include: after forming the reinforcement portion, performing a hydrothermal treatment by injecting 5% to 15% of water vapor by volume therein at a temperature in the range of 600° C. to 900° C. for 1 hour to 96 hours. Specifically, performing the hydrothermal treatment may be performed as follows: performing the hydrothermal treatment after injecting 5% to 15% of water vapor by volume at a temperature in the range of 600° C. to 800° C., in the range of 600° C. to 750° C., in the range of 600° C. to 700° C., or in the range of 700° C. to 800° C. for 1 hour to 72 hours, 1 hour to 36 hours, or 5 hours to 30 hours. In this regard, the hourly gas flow rate of the simulated exhaust gas containing water vapor to the weight of the hydrocarbon adsorption and desorption composite may be in the range of 10,000 mL / g·h to 200,000 mL / g·h, or in the range of 100,000 mL / g·h to 200,000 mL / g·h. The above situation is a serious situation similar to the situation in the case where the vehicle is running for a long time.

[0071] Although the hydrocarbon adsorption and desorption composite that has undergone hydrothermal treatment shows a lower hydrocarbon treatment efficiency compared to the hydrocarbon adsorption and desorption composite that has not undergone hydrothermal treatment, the hydrocarbon adsorption and desorption composite including a reinforcing part made of silica zeolite shows improved heat resistance after hydrothermal treatment and exhibits excellent adsorption and oxidation capabilities compared to the existing hydrocarbon adsorption and desorption composite having only a gas adsorption part.

[0072] In addition, the present disclosure provides a hydrocarbon adsorption and desorption composite for a vehicle, including the hydrocarbon adsorption and desorption composite described above. The hydrocarbon adsorption and desorption composite according to the present disclosure exhibits excellent adsorption capacity, has hydrocarbon oxidation capacity at a temperature of about 200°C (which allows adsorbed hydrocarbons to be oxidized at lower temperatures), and exhibits hydrothermal stability at high temperatures, so that the hydrocarbon adsorption and desorption composite according to the present disclosure can be applied to the removal of exhaust gas of hydrocarbons discharged from vehicles, and can be expected to have an air purification effect by exhibiting excellent hydrocarbon adsorption and oxidation capacity even in the cold start period before the three-way catalyst is sufficiently activated.

[0073] Hereinafter, embodiments of the present disclosure will be described. However, the following embodiments are only preferred embodiments of the present disclosure, and the scope of the present disclosure is not limited by the following embodiments.

[0074] [Example]

[0075] Example 1 (MFI / MFI)

[0076] Zeolite particles of the gas adsorption part were prepared by loading 5 wt% of Cu on H-type ZSM-5 particles having a Si / Al ratio of 10 using a wet impregnation method. A sol solution with a molar ratio of 40TEOS (tetraethyl orthosilicate): 9TPAOH (tetrapropylammonium hydroxide): 9600H2O was prepared and mixed with the zeolite particles of the gas adsorption part so that the ratio of the zeolite particles of the gas adsorption part to the sol solution became 0.3 g / 30 ml to form a mixture. Then, the mixture was placed in a Teflon liner and subjected to hydrothermal synthesis in an oven at 100°C for various time periods (3 hours, 6 hours, 9 hours, 12 hours and 24 hours) to form a reinforcing part on the surface of the gas adsorption part to prepare a hydrocarbon adsorption and desorption composite.

[0077] Example 2 (BEA / BEA)

[0078] Zeolite particles of the gas adsorption part were prepared by loading 5 wt% of Cu on H-type ZSM-5 particles having a Si / Al ratio of 19 using a wet impregnation method. A sol solution with a molar ratio of 1SiO2:0.4TEAOH (tetraethylammonium hydroxide):11.6H2O was prepared and mixed with the zeolite particles of the gas adsorption part so that the ratio of the zeolite particles of the gas adsorption part to the sol solution became 0.3 g / 30 ml to form a mixture. Then, the mixture was placed in a Teflon liner and subjected to hydrothermal synthesis in an oven at 130°C for various time periods (24 hours, 48 ​​hours, and 96 hours) to form a reinforcing portion on the surface of the gas adsorption part to prepare a hydrocarbon adsorption and desorption composite.

[0079] Example 3 (MFI / MFI_HT)

[0080] The hydrocarbon adsorption and desorption composite prepared in Example 1 above was subjected to a hydrothermal treatment using 10% by volume H2O water vapor under an air flow at 800° C. for 24 hours to prepare a hydrocarbon adsorption and desorption composite. In this regard, the hourly gas flow rate of the simulated exhaust gas containing water vapor to the weight of the hydrocarbon adsorption and desorption composite was 100,000 mL·g -1 ·h -1 .

[0081] Example 4 (BEA / BEA_HT)

[0082] The hydrocarbon adsorption and desorption composite prepared in Example 2 above was subjected to a hydrothermal treatment using 10% by volume H2O water vapor under an air flow at 800°C for 24 hours to prepare a hydrocarbon adsorption and desorption composite. In this regard, the hourly gas flow rate of the simulated exhaust gas containing water vapor with respect to the weight of the hydrocarbon adsorption and desorption composite was 100,000 mL·g -1 ·h -1 .

[0083] [Experimental example]

[0084] Experimental Example 1

[0085] In order to identify the form of the hydrocarbon adsorption and desorption composite according to the present disclosure, the hydrocarbon adsorption and desorption composites of Example 1 and Example 2 were photographed with a scanning electron microscope (SEM) and subjected to X-ray diffraction analysis (XRD). The results are shown in Figure 2 and 3 middle.

[0086] exist Figure 2In the figure, as the hydrocarbon adsorption and desorption composite of Example 1, the same kind of silicon zeolite particles are formed on the surface of the gas adsorption part of the zeolite particles containing the MFI framework structure. (a) is a scanning electron microscope image of the gas adsorption part of the zeolite particles with the MFI framework structure loaded with copper ions, (b) is a scanning electron microscope image of the hydrocarbon adsorption and desorption composite prepared by performing the hydrothermal synthesis of the gas adsorption part and the sol solution for 3 hours, (c) is a scanning electron microscope image of the hydrocarbon adsorption and desorption composite prepared by performing the hydrothermal synthesis of the gas adsorption part and the sol solution for 6 hours, and (d) is a scanning electron microscope image of the hydrocarbon adsorption and desorption composite prepared by performing the hydrothermal synthesis of the gas adsorption part and the sol solution for 9 hours. It was identified by the scanning electron microscope images that the form of the silicon zeolite particles of the enhancement part became clear as the synthesis time increased.

[0087] In addition, in the X-ray diffraction analysis graph, even when the time period (hydrothermal synthesis time) for forming the reinforcing portion increases, the X-ray diffraction analysis graph shows an X-ray diffraction analysis graph similar to that of the zeolite having an MFI framework structure. Therefore, it was identified that, regardless of the time period for forming the reinforcing portion, zeolite particles of other forms were not synthesized. Therefore, it can be seen that in the hydrocarbon adsorption and desorption composite of Example 1, there is no zeolite having other structures except the zeolite having an MFI framework structure.

[0088] exist Figure 3 In the figure, as the hydrocarbon adsorption and desorption composite of Example 2, the same kind of silicon zeolite particles are formed on the surface of the gas adsorption part of the zeolite particles containing the BEA framework structure. (a) is a scanning electron microscope image of the gas adsorption part of the zeolite particles with the BEA framework structure loaded with copper ions, (b) is a scanning electron microscope image of the hydrocarbon adsorption and desorption composite prepared by performing the hydrothermal synthesis of the gas adsorption part and the sol solution for 24 hours, (c) is a scanning electron microscope image of the hydrocarbon adsorption and desorption composite prepared by performing the hydrothermal synthesis of the gas adsorption part and the sol solution for 48 hours, and (d) is a scanning electron microscope image of the hydrocarbon adsorption and desorption composite prepared by performing the hydrothermal synthesis of the gas adsorption part and the sol solution for 96 hours. It was identified by the scanning electron microscope images that the form of the silicon zeolite particles of the enhancement part became clear as the synthesis time increased.

[0089] In addition, in the X-ray diffraction analysis graph, even when the time period (hydrothermal synthesis time) for forming the reinforcing portion increases, the X-ray diffraction analysis graph shows an X-ray diffraction analysis graph similar to that of the zeolite having a BEA framework structure. Therefore, it was identified that, regardless of the time period for forming the reinforcing portion, zeolite particles of other forms were not synthesized. Therefore, it can be seen that in the hydrocarbon adsorption and desorption composite of Example 2, there is no zeolite having other structures except the zeolite having a BEA framework structure.

[0090] Experimental Example 2

[0091] In order to identify the hydrocarbon adsorption amount and hydrocarbon treatment efficiency based on the enhanced partial synthesis time of the hydrocarbon adsorption and desorption composite according to the present disclosure, a cold start test (CST) was performed on the hydrocarbon adsorption and desorption composites of Example 1 and Example 2 with respect to each enhanced partial synthesis time, and the results are shown in Figures 4 to 6 and Table 1.

[0092] [Table 1]

[0093]

[0094]

[0095] In the cold start test, 100 mL / min of simulated exhaust gas feed was flowed to 0.06 g of zeolite pellets that had been pretreated at 600°C for 30 minutes under 30 mL / min He conditions. In this regard, the simulated exhaust gas feed consisted of 100 ppm propylene, 100 ppm toluene, 1 vol% oxygen (O2), 10 vol% water vapor (H2O) and helium (He balance) 100 mL / min and had a 100,000 mL·g -1 ·h -1 The zeolite particles were exposed to a simulated exhaust gas feed at 70°C for 5 minutes, heated at a heating rate of 53°C / min, and then exposed to a simulated exhaust gas feed at 600°C for 5 minutes. The adsorption and desorption behaviors of propylene and toluene of hydrocarbons and total hydrocarbons were identified.

[0096] In Table 1, the adsorption amount until the concentration of the discharged total hydrocarbons equals the methane concentration (inlet concentration, 1000 ppm) corresponding to propylene and toluene is calculated as the total hydrocarbon adsorption amount.

[0097] Figure 4 A graph showing the results of cold start tests for each hydrocarbon adsorption and desorption composite of Examples 1 and 3 prepared with enhanced portion synthesis times of 3 hours, 6 hours, 9 hours, 12 hours, and 24 hours.

[0098] Figure 5Graphs showing changes in the enhancement portion synthesis time, the weight ratio of the enhancement portion to the gas adsorption portion (left), and the hydrocarbon treatment efficiency (right) of the hydrocarbon adsorption and desorption composites based on Examples 1 and 3.

[0099] In Table 1, Figure 4 and Figure 5 In the case of the hydrocarbon adsorption and desorption composite of Example 1 which was not subjected to hydrothermal treatment, it was determined that the propylene adsorption amount decreased and the toluene desorption amount increased as the synthesis time of the enhancement part increased, and it was determined that the overall hydrocarbon treatment efficiency decreased as the synthesis time of the enhancement part increased. This is related to the increase in the weight ratio of the enhancement part to the gas adsorption part as the synthesis time of the enhancement part increases.

[0100] In addition, it was determined that the hydrocarbon adsorption and desorption composite of Example 3 treated at 800°C for 24 hours under the condition of a gas flow mixed with 10% by volume H2O, when only the gas adsorption part was present, could not exhibit hydrocarbon adsorption performance after hydrothermal treatment because the enhancement part was not formed. However, it was determined that the adsorption performance of propylene and toluene gradually improved and then decreased when the enhancement part was formed. Figure 5 It can be seen from the overall hydrocarbon treatment efficiency in that as the synthesis time of the enhancement part increases, the overall hydrocarbon treatment efficiency of the particles that have been hydrothermally treated increases compared to the hydrocarbon adsorption and desorption composite of Example 1 that has not been hydrothermally treated. In particular, it can be seen that when the enhancement part is formed for 24 hours, the hydrothermal stability is improved with the formation of the enhancement part, and it can be seen that the overall hydrocarbon efficiency of the composite that has not been hydrothermally treated and the composite that has been hydrothermally treated are almost the same.

[0101] Figure 6 A graph showing the results of cold start tests for each hydrocarbon adsorption and desorption composite of Examples 2 and 4 prepared with enhanced portion synthesis times of 24 hours, 48 ​​hours, and 96 hours.

[0102] Figure 7 Graphs showing the changes in enhancement portion synthesis time, weight ratio of the enhancement portion to the gas adsorption portion (left), and overall hydrocarbon treatment efficiency (right) for hydrocarbon adsorption and desorption composites based on Examples 2 and 4.

[0103] In Table 1, Figure 6 and Figure 7 In the case of the hydrocarbon adsorption and desorption composite of Example 2 which was not subjected to hydrothermal treatment, it was determined that the amount of propylene adsorption decreased after the synthesis time of the enhanced portion, but the overall hydrocarbon treatment efficiency was similar regardless of the synthesis time of the enhanced portion. Therefore, it can be seen that this is related to the fact that the overall hydrocarbon treatment efficiency is similar regardless of the synthesis time of the enhanced portion,

[0104] Furthermore, it was determined that the hydrocarbon adsorption and desorption composite of Example 4 treated at 800°C for 24 hours under the condition of a gas flow mixed with 10 vol% H2O, when only the gas adsorption portion was present, could not exhibit hydrocarbon adsorption performance after the hydrothermal treatment because the enhancement portion was not formed. However, it was determined that the adsorption performance of propylene and toluene improved when the enhancement portion was formed, and in particular, the adsorption performance of propylene and toluene was the best when the enhancement portion was formed for 24 hours, and then, as the synthesis time of the enhancement portion increased, the adsorption amount of propylene and toluene gradually decreased. Figure 7 In the overall hydrocarbon processing efficiency of , it was determined that the hydrocarbon adsorption and desorption composite synthesized for 24 hours of the enhancement portion showed the highest overall hydrocarbon processing efficiency after hydrothermal treatment. As in Example 1, it can be seen that there is a range of enhancement portion synthesis time that shows hydrothermal stability while showing the best overall hydrocarbon processing efficiency.

[0105] Therefore, the hydrocarbon adsorption and desorption composite according to the present disclosure can adjust the ratio of the enhancement part to the gas adsorption part by controlling the synthesis time of the enhancement part, thereby improving the hydrocarbon adsorption capacity and hydrothermal stability of the composite at the same time compared with the existing hydrocarbon adsorption and desorption composite composed only of the gas adsorption part.

Claims

1. A hydrocarbon adsorption and desorption composite comprising: a gas adsorption portion comprising zeolite particles, wherein the zeolite particles have a silicon to aluminum molar ratio in the range of 5 to 40; and a reinforcing portion formed on the surface of the gas adsorption portion, wherein the reinforcing portion contains silicalite particles having the same structure as the zeolite particles of the gas adsorption portion, wherein metal ions are bound to the inside of pores present in the zeolite particles of the gas adsorption portion, and a metal oxide is arranged at an interface between the silicalite particles of the reinforcement portion and the gas adsorption portion, wherein the zeolite particles of the gas adsorption part are independently at least one zeolite selected from the group consisting of MFI, β, MOR, FAU, FER, SFW and LTA, and wherein the hydrocarbon adsorption and desorption composite has a weight ratio of the enhancing portion to the gas adsorbing portion in the range of 15 to 80, The volume of the micropores of the zeolite particles in the gas adsorption part is 0.1 cm 3 / g to 0.18cm 3 / g range, wherein the metal ion is a cation of one of iron, cobalt, nickel, copper, zinc and cadmium, and the metal oxide is an oxide of one of iron, cobalt, nickel, copper, zinc and cadmium, wherein the reinforcing portion is formed by adding the zeolite particles of the gas adsorption portion into a sol solution and performing hydrothermal synthesis on the sol solution for 4 hours to 96 hours, wherein the sol solution has a molar ratio of silicon precursor:structure directing agent:solvent of 10:1 to 15:10 to 50000, and has a mixing ratio of the gas adsorption part to the sol solution in the range of 0.03 g / 30 mL to 3 g / 30 mL, Wherein, the hydrocarbon adsorption and desorption complex satisfies the following formula 1: [Formula 1] In the above formula 1, Q In represents the total amount of hydrocarbons injected into the hydrocarbon adsorbent when the temperature reaches 300°C, Q Out represents the total amount of hydrocarbons emitted through the hydrocarbon adsorbent when the temperature reaches 300°C, and A is a number equal to or greater than 10, and represents hydrocarbon processing efficiency.

2. The hydrocarbon adsorption and desorption composite according to claim 1, wherein: The hydrocarbon adsorption and desorption composite is further subjected to a hydrothermal treatment using 5 to 15% by volume of water vapor at a temperature ranging from 600° C. to 900° C. for 1 to 96 hours.

3. The hydrocarbon adsorption and desorption composite according to claim 1, wherein: The size of the hydrocarbon adsorption and desorption complex is in the range of 50 nm to 5000 nm, Wherein, the size of the metal oxide is in the range of 1 nm to 10 nm.

4. The hydrocarbon adsorption and desorption composite according to claim 1, wherein: The hydrocarbon adsorption and desorption composite exhibits adsorption capability at a temperature equal to or lower than 300°C, and exhibits oxidation capability at a temperature equal to or higher than 180°C.

5. The hydrocarbon adsorption and desorption composite according to claim 1, wherein: The hydrocarbon adsorption and desorption complex has a CH4 / g to 1.5mmol CH4 / g range of hydrocarbon adsorption, Wherein, the hydrocarbon adsorption and desorption composite has a hydrocarbon oxidation onset temperature in the range of 180°C to 350°C.

6. A method for preparing the hydrocarbon adsorption and desorption composite according to claim 1, the method comprising: forming the gas adsorption portion by mixing the zeolite particles with a solution containing metal ions and then calcining the mixture; and adding the zeolite particles of the gas adsorption part to a sol solution containing a silicon precursor and a structure directing agent, and performing hydrothermal synthesis on the sol solution for 4 to 96 hours to form the reinforcement part, wherein the molar ratio of silicon to aluminum of the zeolite particles of the gas adsorption portion is in the range of 5 to 40, The volume of the micropores of the zeolite particles in the gas adsorption part is 0.1 cm 3 / g to 0.18cm 3 / g range, wherein the metal ion is a cation of one of iron, cobalt, nickel, copper, zinc and cadmium, and the metal oxide is an oxide of one of iron, cobalt, nickel, copper, zinc and cadmium, The sol solution has a molar ratio of silicon precursor:structure directing agent:solvent of 10:1 to 15:10 to 50000, and has a mixing ratio of the gas adsorption part to the sol solution in the range of 0.03 g / 30 mL to 3 g / 30 mL.

7. The method according to claim 6, wherein: The structure directing agent is at least one selected from the group consisting of tetrapropylammonium hydroxide, tetraethylammonium hydroxide, N,N,N-trimethyladamantylammonium hydroxide, N,N,N-trimethyladamantylammonium bromide, N,N,N-trimethyladamantylammonium fluoride, N,N,N-trimethyladamantylammonium chloride, N,N,N-trimethyladamantylammonium iodide, tetraethylammonium bromide, tetraethylammonium fluoride, tetraethylammonium chloride, tetraethylammonium iodide, tetrapropylammonium bromide, tetrabutylphosphonium hydroxide, tetrabutylammonium chloride, tetrabutylammonium hydroxide, tetrabutylammonium fluoride and cyclohexylamine.

8. The method according to claim 6, further comprising: After forming the reinforcement portion, hydrothermal treatment is performed by injecting 5 to 15% by volume of water vapor into the hydrocarbon adsorption and desorption composite at a temperature ranging from 600° C. to 900° C. for 1 to 96 hours.

9. Use of the hydrocarbon adsorption and desorption composite according to any one of claims 1 to 5 for the removal of hydrocarbon tail gas emitted by vehicles.

Citation Information

Patent Citations

  • Adsorbent medium containing lithium-exchanged zeolite

    JP2012512022A

  • NOx (Nitrogen Oxide) adsorbent as well as preparation method and application thereof

    CN109759035A

  • Preparation method of adhesive-free pure siliceous silicalite-3 adsorbent

    CN111482157A

  • Hydrocarbon adsorbent with metal-impregnated zeolite particle having regular mesopore and manufacturing method therefor

    CN111542388A